Analisis Tren Pengobatan Ruqyah dengan Daun Bidara: Studi Takhrij dan Syarah Hadis Pendekatan Kontemporer - Cep Imam Ashabulyamin; Hidayatul Fikra; Dadah Dadah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to analyze the hadith about the use of bidara leaves for the treatment of ruqyah. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of this study found that the quality status of the hadith about bidara leaves was considered authentic based on the takhrij hadith. Syarah hadith shows that at the time of the Prophet Muhammad. The bidara leaves are used to bathe the corpse, bathing is obligatory for women who have finished their menstruation and for people who have just embraced Islam. In today's era, bidara leaves are used as a medium for ruqyah with the aim of expelling the jinn by bathing them in trance patients so that the jinn in the patient's body are easily removed. This study concludes that the hadith about bidara leaves is acceptable (maqbul) so that it can be used as evidence for Islamic practice.